1986
DOI: 10.1007/bf00870139
|View full text |Cite
|
Sign up to set email alerts
|

The immune response to influenza vaccination in diabetic patients

Abstract: The immune response of diabetic patients to influenza vaccination was examined in 31 patients, 10 with Type 1 (insulin-dependent) diabetes and 21 with Type 2 (non-insulin-dependent diabetes), and in 19 normal subjects. Each received a single intramuscular injection of the 3 virus strains (A/Chile,A/Philippines,B/USSR) anti-influenza vaccine recommended by WHO. The antibody titre and the cell-mediated immune response to the 3 virus strains, as evaluated by the generation of activated lymphocytes and enumeration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0
1

Year Published

1987
1987
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 20 publications
1
46
0
1
Order By: Relevance
“…22 Another study in patients with well-controlled diabetes showed that humoral and cellmediated immune responses to seasonal influenza vaccine were normal and immune response did not differ from those observed in age-matched normal subjects. 23 A third study showed that diabetic patients in the older age range or with longer disease duration showed a lower sero-conversion proportion with A(H1N1)pdm09 vaccine. 24 Such results are broadly consistent with our findings that immunity was sufficient as a whole, but older age, decreased BMI and increased HbA1c level were associated with poor immunogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…22 Another study in patients with well-controlled diabetes showed that humoral and cellmediated immune responses to seasonal influenza vaccine were normal and immune response did not differ from those observed in age-matched normal subjects. 23 A third study showed that diabetic patients in the older age range or with longer disease duration showed a lower sero-conversion proportion with A(H1N1)pdm09 vaccine. 24 Such results are broadly consistent with our findings that immunity was sufficient as a whole, but older age, decreased BMI and increased HbA1c level were associated with poor immunogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, the antigen-binding fragment of IgG was glycosylated in preference to the effector fragment [34]. The clinical relevance of these observations is unclear since the antibody response and protection after vaccination against the common infections, influenza, pneumococcal infection and hepatitis B show adequate responses in patients with diabetes [35][36][37][38][39][40][41][42][43][44]. Thus, we support the recommendation that adult diabetic patients receive the influenza vaccine before every epidemic season and the polysaccharide pneumococcal vaccine on one occasion followed by a booster at 5 years [45][46][47][48][49].…”
Section: Adaptive Immunitymentioning
confidence: 99%
“…Many studies have shown that diabetic individuals have an immune response to influenza vaccination similar to that of healthy controls, while a few studies have reported suboptimal responses in diabetic subjects (6)(7)(8)(9)(10)(11)(12). Immunogenicity should be maintained throughout the entire seasonal epidemic; therefore, an evaluation of longterm immunogenicity is essential before the current conventional vaccination program can be recommended.…”
mentioning
confidence: 99%